Antimicrobial Prescribing in the Telehealth Setting: Framework for Stewardship During a Period of Rapid Acceleration Within Primary Care. (30th July 2022) - Sine, Kathryn; Appaneal, Haley; Dosa, David; LaPlante, Kerry L
Abstract: Antibiotic resistance is a global public health threat. The use of telehealth in primary care presents unique barriers to antimicrobial stewardship, including limited physical examination and changes to the patient-provider relationship. Since the coronavirus disease 2019 (COVID-19) pandemic, there is a need to identify novel antimicrobial stewardship strategies with an explosion in the use of telehealth within primary care. Our review proposes a tailored, sustainable approach to antimicrobial prescribing in the telehealth setting based on the Centers for Disease Control and Prevention's Core Elements of Outpatient Antibiotic Stewardship: commitment, action for policy and practice; tracking and reporting; and education and expertise. The rapid growth of telehealth for all types of primary care visits (not just antibiotic use) is outpacing knowledge associated with strategies for antimicrobial stewardship. Improving antibiotic use within primary care settings is critical as telehealth will remain a priority whether the COVID-19 pandemic recedes, particularly within patient populations with limited access to healthcare. Abstract : Our review proposes a tailored, sustainable approach to antimicrobial stewardship for primary care settings using telehealth based on the CDC's 4 Core Elements of Outpatient Antimicrobial Stewardship: commitment, action for policy and practice; tracking and reporting; and education and expertise.